Peramalan Permintaan Pada Toko Mainan Prima Acc & Toys Menggunakan Metode Simple Moving Average - Azizah Baldah; Sandhy Fernandez; Febri Cintya Maharani; Hetty Kristina Gultom (Journal of Information System Research (JOSH), 2022)
Sales success is seen from the sales strategy. As an entrepreneur in the field of sales, you must be able to take decisive steps in the field of sales in maximizing benefits. The demand for an item is unpredictable, so intuition and experience alone are not enough to determine the inventory of each item to be sold. If you only rely on intuition and experience, and all items are not sold, it will cause waste and losses, but if the turnover of goods is fast and inventory is not on time, it will affect the financial turnover of the store. The application of the Simple Moving Average method at the Prima Acc store can help store owners to be more efficient in incoming and outgoing goods so that losses that may occur at the Prima Acc store can be avoided because store owners already know the forecast demand for goods in the future. The author suggests that the choice of forecasting demand for this process uses the 3 month moving average method with 38 predictions. The estimated error accuracy of MAE is 9.63 and MSE is 123.51.